1998
DOI: 10.1109/36.701021
|View full text |Cite
|
Sign up to set email alerts
|

Prelaunch algorithm and data format for the Level 1 calibration products for the EOS-AM1 Moderate Resolution Imaging Spectroradiometer (MODIS)

Abstract: ABSTRACT--TheMODIS radiometric calibration product (Level 1B) is described for the thermal emissive and the reflective solar bands. Specific sensor design characteristics are identified to assist in understanding how the calibration algorithm software product is designed. The reflected solar band software products of radiance and reflectance factor both are described. The product file format is summarized and the MCST Homepage location for the current file format is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 4 publications
0
44
0
Order By: Relevance
“…The 250-m bands are centered at 0.65 and 0.86 m with the 500-m bands at 0.47, 0.56, 1.24, 1.63, and 2.13 m. Each band's spectral response is determined by an interference filter overlying a detector array imaging a 10-km along-track scene for each scan (i.e., 40, 20, and 10 element arrays for the 250, 500, and 1000-m bands, respectively). MODIS has several onboard instruments for in-orbit radiometric and spectral characterization [5], [6]. Of particular importance to the cloud optical and microphysical algorithms, which are fundamentally based on solar reflectance values and not radiance, is a solar diffuser panel for reflectance calibration up through the 2.1-m MODIS band and an accompanying diffuser stability monitor for assessing the stability of the diffuser up to 1 m.…”
mentioning
confidence: 99%
“…The 250-m bands are centered at 0.65 and 0.86 m with the 500-m bands at 0.47, 0.56, 1.24, 1.63, and 2.13 m. Each band's spectral response is determined by an interference filter overlying a detector array imaging a 10-km along-track scene for each scan (i.e., 40, 20, and 10 element arrays for the 250, 500, and 1000-m bands, respectively). MODIS has several onboard instruments for in-orbit radiometric and spectral characterization [5], [6]. Of particular importance to the cloud optical and microphysical algorithms, which are fundamentally based on solar reflectance values and not radiance, is a solar diffuser panel for reflectance calibration up through the 2.1-m MODIS band and an accompanying diffuser stability monitor for assessing the stability of the diffuser up to 1 m.…”
mentioning
confidence: 99%
“…The Gaussian distributed random noises were simulated. From the specified description of the MODIS infrared channels (Guenther et al 1998), the standard deviations were found to be 0.05, 0.01 and 0.005 K for channels 2.1, 4.0 and 11.0 µm, respectively.…”
Section: Data Simulationmentioning
confidence: 99%
“…To unify to the angle's data, the first band (red band) data of MODIS are extracted from MOD02 and MYD02 products (Level-1B Calibrated Geolocation Data Set), in which the resolution is aggregated to 1 km. In MOD03, MYD03, MOD02 and MYD02 products, MOD is for TERRA, and MYD is for AQUA [30].…”
Section: Retrieval Of Hod Based On Satellite Remote Sensing In Clear mentioning
confidence: 99%